Portable Circulating Adsorption Column Design for Seawater Purification - Mohammad Prasanto Bimantio; Amallia Ferhat (OPSI, 2021)
Seawater is one of the largest natural resources and abundant in Indonesia, which contains salt, metals and mycobacteria. Even though the amount is abundant, its utilization is still not widespread, such as to be used as clean water or drinking water. The use of adsorbents aims to adsorb impurities in the fluid. The adsorption column that is widely used is in the form of a fixed-bed column with messy stacked filling. This makes it difficult to clean and fill the adsorbent, besides the irregular pile of adsorbents will hinder the flow process of the purified fluid. The research product is a circulating portable adsorption column design consisting of 3 parts, namely: top distributor, packing bed, and bottom collector. The principle of the three parts is like a puzzle where the number of packing beds can be adjusted according to the purification needs. The three parts are connected with threads so that they can be disassembled as desired. It is hoped that this product can meet the needs of adsorption-based purification that is easy, inexpensive, and can be customized according to various types of adsorbents. The design of this product can be duplicated for other adsorption purification processes, such as purification of bioethanol, wastewater, and biodiesel.